Strengthening village community empowerment by optimizing ecotourism with participatory approach in Bumiaji - Priambodo Magistyo P.; Wahjoedi; Ibnu Abbas Muhammad H.; Yunikawati Nur A.; Prastiwi Lustina F. (E3S Web of Conferences, 2022)
The development of tourism has brought many changes in economic activity. Region with tourism objects will create jobs opportunity and improve the quality of infrastructure to support it. Bumiaji is one of the areas in Batu City which has many natural tourist attractions. Development of tourism in Bumiaji leads to ecotourism which favored by local people and outsiders. The natural potential supporting ecotourism emerge to be developed. This study reveals how the community empowerment strategy implemented by the government for developing ecotourism villages and how community participation’s level in the Ecology based Tourism Village in Bumiaji. The purpose of this study was to determine the strategy of strengthening empowerment and to determine community participation in the development of ecotourism village. This type of research is a field research using a qualitative approach with descriptive analysis. Sources of data in this study consisted of primer data and participants responses obtained through interviews, observation and documentation. Findings of the research stated that the strategy of increasing community empowerment which was accommodate by government to develop Bumiaji Ecological Tourism Village, was through a strategy with the stages of awareness, capacity, and empowerment. The local community in the Bumiaji Ecological Tourism Village also highly participates in supporting the optimization of ecotourism in all aspect.